Assessing the Condition of Domestic Child Workers Aftermath of Nepal Earthquake in Besisahar Municipality, Lamjung - Baral, Chhabi Ram (Patan Pragya, 2020)
Domestic Child Workers are a familiar and a serious problem throughout the world. It is also common wide-spread phenomena and emerging issue not only in urban areas but also in rural setting in Nepal. Domestic child workers are not only the problem of an individual or a family but also the common problem of the society. In this context, the main objective of this paper is to examine the major problems, health situation, and assess the working conditions of domestic child workers aftermath of April 25th, 2015 earthquake disaster in Besisahar Municipality, Lamjung, Nepal. The data and information needed for this study were obtained through the mix method with primary and secondary sources. Study finds that the education level of child domestic workers is very poor. Poverty is one of the major causes for children being engaged in domestic child worker. Based on findings the overall condition for the domestic child workers in terms of basic needs like food, shelter, clothes and health was found critical.